Analyzing the Curriculum: The Relationship Between Rote-Based Education and Laboratory Course Hours in Public Anatolian High Schools in Bursa, Turkey (European Journal of Teaching and Education, 2022)
This study is a qualitative design that investigates the relationship between the rote-based education and the laboratory lesson hours in public Anatolian high schools located in Bursa, Turkey. Additionally, this investigation is carried out by personal surveys which were asked to high school students who are currently studying at public high schools in Bursa. Particularly, this research focuses on the Anatolian high schools which were located in three different districts of Bursa because the presence of Anatolian high schools within those regions is much more frequent than in some other districts. The main focus is to find a relationship between the laboratory hours in public Anatolian high schools in Bursa and correlate it with the rote-based education. While obtaining the data, students who are studying at public Anatolian high schools from different districts of Bursa were asked questions about the laboratory course hours within the school’s curriculum, availability of equipped laboratories, and the presence of experimentation methods in science lessons. The responses to the questions from the students indicated that a relationship between the rote-based education can be related to the observed lab hours in public Anatolian high schools in Bursa, Turkey. After processing the data, it was found that there is a correlation between the rote education and lab hours where schools design their curricula based on the methods of scoring high in the national university entrance exam.